The Potential of Florida Lychee to Cross Over to American Consumers: An Industry Perspective - A. R. Rafie; Carlos Balerdi; Jonathan Crane (EDIS)
HS-1112, a 3-page illustrated fact sheet by A.R. Rafie, Carlos Balerdi, and Jonathan Crane, presents the findings of surveys of consumers and industry to determine their assessment of lychee's potential to appeal to American consumers and eventually to become as popular as other tropical fruits such as pineapple and mango. Published by the UF Department of Horticultural Sciences, August 2007.